Caractéristiques sociodémographiques des minorités visibles - RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
Ce document présente une série de tableaux illustrant les principales variables sociodémographiques des populations de minorités visibles au sein des groupes linguistiques de RTS de la Mauricie-et-du-Centre-du-Québec.

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2024)

Socio-Demographic Characteristics of Visible Minorities in RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2024)
This document presents a series of tables illustrating key socio-demographic variables of visible minority populations within language groups for RTS de la Mauricie-et-du-Centre-du-Québec.

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Population Aged 15 to 29 Years, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Population âgée de 15 à 29 ans, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Population totale, 2021 - Community Health and Social Services Network (CHSSN) (2024)

RTS de la Mauricie-et-du-Centre-du-Québec - Total Population, 2021 - Community Health and Social Services Network (CHSSN) (2024)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Le temps d’un thé : À la rencontre des familles fondatrices - Centre for Access to Services in English (CASE) (2023)

Remembering Drummondville’s First Families : A Very Special Heritage Tea and Talk - Centre for Access to Services in English (CASE) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

CASE-MCQ and St.George’s Church Foundation Present : Stained-Glass and Savoir-Faire : A Tea and Talk about the Restoration of St. George’s Stained-glass Windows - Centre for Access to Services in English (CASE); St. George's Church Foundation (2023)

CASE-MCQ et la Fondation St. George présentent : Savoir-faire et Lumière : Une conférence sur le projet de restauration des vitraux de l’église St. George - Centre for Access to Services in English (CASE); St. George's Church Foundation (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

CASE-MCQ and St.George’s Church Foundation Present : Bonjour, Olá : An Evening of Classical Guitar and Percussion, From Québec to Brazil - Centre for Access to Services in English (CASE); St. George's Church Foundation (2023)

CASE-MCQ et la Fondation St. George présentent : Bonjour, Olá : Une soirée de guitare classique et de marimba, du Québec au Brésil - Centre for Access to Services in English (CASE); St. George's Church Foundation (2023)

Partners in Health - Centre for Access to Services in English (CASE) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Blue Skies : An Evening of Jazz and R&B - Centre for Access to Services in English (CASE) (2023)

Down Home News - Megantic English-speaking Community Development Corporation (MCDC) (2023)

Demographic Profiles of Québec's English-speaking Communities Region of Centre-du-Québec and MRC Arthabaska - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of Québec's English-speaking Communities RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Baseline Data Report Series, 2023)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2021 Census of Canada and organized by province and RTS territories. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Québec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Partners in Health - Centre for Access to Services in English (CASE) (2022)

Concert de Noël : Chants et souvenirs de Noël - Centre for Access to Services in English (CASE) (2022)

Partners in Health - Centre for Access to Services in English (CASE) (2022)

Récits d’un petit “shtetl” : histoire de la communauté juive de Drummondville - Miller, Julie (2022)

Stories of a Small “Shtetl” : Jewish History in Drummondville - Miller, Julie (2022)

Partners in Health - Centre for Access to Services in English (CASE) (2022)

Money Raised for La Rose des Vents de Drummond and a Successful First Edition of the “History and Music” Concert Series - Centre for Access to Services in English (CASE) (2022)

Partners in Health - Centre for Access to Services in English (CASE) (2022)

Concert Series to Highlight Talents of Young Musicians Celebrating Local Heritage in the Sonorous Acoustics of St George Anglican Church - Centre for Access to Services in English (CASE) (2022)

Employment Profile of English Speakers in Centre-du-Québec - Provincial Employment Roundtable (PERT) (2022)
This profile aims to contribute to the knowledge and understanding of the employment issues faced by Capitale-Nationale’s English-speaking communities by surveying the most comprehensive information on the demographic and labour force conditions of English speakers in the region. The profile compiles the available data on English speakers’ employment status with respect to their position as linguistic minorities in majority French-speaking communities. For this reason, most of the information presented in this profile is organized by the two linguistic categories of English speakers and French speakers. In addition to examining the demographics and labour force of the English-speaking population, this profile also surveys Capitale-Nationale’s economic structure, as well as the work activity, income, and educational attainment of workers with the goal of providing a more holistic picture of employment and employability.

Profil d'emploi des Québécois d'expression anglaise au Centre-du-Québec - Provincial Employment Roundtable (PERT) (2022)
Ce profil a pour but de contribuer à la connaissance et à la compréhension des difficultés en matière d’emploi auxquelles font face les communautés d’expression anglaise du Centre-du-Québec en analysant les informations les plus complètes sur la démographie et les conditions de travail des personnes d’expression anglaise du Centre-du-Québec. Le profil compile les données disponibles sur le statut d’emploi des personnes d’expression anglaise par rapport à leur position de minorité linguistique au sein de communautés majoritairement francophones. Par conséquent, la plupart des informations présentées dans ce profil sont organisées selon ces deux catégories linguistiques; personnes d’expression anglaise et personnes d’expression française. En plus d’examiner les données démographiques et les conditions de travail de la population d’expression anglaise, ce profil analyse la structure économique du Centre-du-Québec, de même que l’activité professionnelle, le revenu et le niveau d’éducation des travailleurs dans le but d’en dresser un portrait d’emploi et d’employabilité complet.

"Carols and Christmas Memories" : A Holiday Community Concert Featuring Familiar Tunes and Personal Tales of Christmases Past - Centre for Access to Services in English (CASE) (2021)

Partners in Health - Centre for Access to Services in English (CASE) (2021)

Hats and High Tea : Local Collector to Share "Mobile Museum" in Bilingual Talk Highlighting the History of Fashion from 1940-1965, Followed by a Traditional English-style High Tea - Centre for Access to Services in English (CASE) (2021)

Peer-reviewed by Fifth-graders : International Science Journal Brings Drummondville Students to the Frontier of Cutting Edge Discoveries - Centre for Access to Services in English (CASE) (2021)

Over 450 Years of Song: Religious Heritage Days Concert - Centre for Access to Services in English (CASE) (2021)

Partners in Health - Centre for Access to Services in English (CASE) (2021)

Partners in Health - Centre for Access to Services in English (CASE) (2021)

Partners in Health - Centre for Access to Services in English (CASE) (2021)

Window Onto Local Farming : Être femme en agriculture / Women in Agriculture - Miller, Julie; Lapierre, Carole-Anne (2021)

Raise a Glass to the Season! : CASE-MCQ Invites You to an Evening of Stories, Music and Conversation with Rob Lutes - Centre for Access to Services in English (CASE) (2020)

End of the Year Recipe Exchange : 2020-2021 - Centre for Access to Services in English (CASE) (2020)

Partners in Health - Centre for Access to Services in English (CASE) (2020)

$40,000 Awarded in Student Leadership Bursaries for the Mauricie/Centre-du-Québec Region - Miller, Julie; Vidal, Emily (2020)

Fall Colours Acoustic Concert - Cancelled Due to COVID-19 - Centre for Access to Services in English (CASE) (2020)

Case Welcomes Three New Employees - Centre for Access to Services in English (CASE) (2020)

Partners in Health - Centre for Access to Services in English (CASE) (2020)

Caregivers' Guide : Local and Regional Resources for Caregivers in the Centre-du-Québec - Centre for Access to Services in English (CASE) (2020)
The Institut de la Statistique du Québec states that as of 2015 as many as a quarter of the population of Québec were caregivers, the majority being female, for people with long-term health complications. The recipient of the care is most often a family member. The reason for needing care varies between chronic illness, disability, and difficulties related to aging. Of those providing care to family members, greater than one third act as a caregiver to more than one person.

Partners in Health - Centre for Access to Services in English (CASE) (2020)

Partners in Health - Centre for Access to Services in English (CASE) (2020)

Annual Report 2019-2020 : Learning in the Next Decade of Education - Leading English Education and Resource Network (LEARN) (2020)

Partners in Health - Centre for Access to Services in English (CASE) (2019)

Partners in Health - Centre for Access to Services in English (CASE) (2019)

Partners in Health - Centre for Access to Services in English (CASE) (2019)

Partners in Health - Centre for Access to Services in English (CASE) (2019)

Annual Report 2018-2019 - Leading English Education and Resource Network (LEARN) (2019)

Partners in Health - Centre for Access to Services in English (CASE) (2018)

Partners in Health - Centre for Access to Services in English (CASE) (2018)

Demographic Profile of the English-speaking Communities in the Administrative Region of Centre-du-Québec & MRC Arthabaska - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Demographic Profile of the English-speaking Communities in the Administrative Region of Centre-du-Québec & MRC Drummond - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2018)
The MRC Profile Series is intended to serve as a resource that will allow local communities to better understand the demographic factors affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. This series presents selected demographic characteristics of the English-speaking population residing in the MRC or MRC-equivalent territories. The data is drawn from a series of tables developed by the Community Health and Social Services Network (CHSSN) based on the 2016 Census of Canada. The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s English-speaking minority communities.

Annual Report 2017-2018 : Leading the Way - Leading English Education and Resource Network (LEARN) (2018)

Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

Annual Report 2016-2017 - Leading English Education and Resource Network (LEARN) (2017)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS d'Arthabaska-de l'Érable (0418) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Bécancour - Nicolet-Yamaska (0416) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Drummond (0417) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS de Trois-Rivières (0415) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS du Centre-de-la-Mauricie (0414) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

Demographic Profiles of English-speaking Communities : RTS de la Mauricie-et-du-Centre-du-Québec & RLS du Haut-Saint-Maurice (0411) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2017)
This volume of the Baseline Data Report (BDR) series presents demographic characteristics of the English-speaking population residing in the areas covered by the organizations participating in the Networking and Partnership Initiative (NPI). The information presented is drawn from the 2016 Census of Canada and organized by province and RTS and RLS territories (see section below for regional definitions). The selection of characteristics is guided by their importance as determinants of the health status and vitality of Quebec’s official language minority community.
Keywords: Official Language Minority Community (OLMC)

CLC Chronicles 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)

Invitation aux media : Conférence de presse - Centre for Access to Services in English (CASE) (2016)

Update - Leading English Education and Resource Network (LEARN) (2016)

Year-End Report - Leading English Education and Resource Network (LEARN) (2016)
The Leading English Education and Resource Network (LEARN) is a non-profit organization that serves the public, private, anglophone and aboriginal Youth and Adult Education sectors of Québec. We bring together the expertise and efforts of educators, students, parents and partners in our community to cultivate success for all learners.

Children 0 to 5 and their Parents : RTS de la Mauricie-et-du-Centre-du-Québec - Community Health and Social Services Network (CHSSN) (2016)

Provincial Resource Team Report 2015-2016 - Leading English Education and Resource Network (LEARN) (2016)
Over the last ten years, English schools in Quebec have increasingly embraced the dual role of supporting student perseverance and contributing to the vitality of their English-speaking communities. With more than 80 schools and adult education centres across the province now part of the Community Learning Centre (CLC) network, it is evident that School Boards are adopting a new way of thinking about school and community partnerships. This “integrated focus on academics, services, supports and opportunities leads to improved student learning, stronger families and healthier communities. Schools become centers of the community”
Keywords: Official Language Minority Community (OLMC)

CLC Initiative Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2015)
Keywords: Official Language Minority Community (OLMC)

2013-2014 Annual Report of CLC Activities - Leading English Education and Resource Network (LEARN) (2014)
Keywords: Official Language Minority Community (OLMC)

June 12, 2014 - Leading English Education and Resource Network (LEARN) (2014)

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CLSC Arthabaska (04081) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Arthabaska Erable (0408) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Becancour Nicolet Yamaska (0406) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Baseline Data Report 2013-2014 : Demographic Profile of the English-speaking Communities of CSSS de Drummond (0407) - Pocock, Joanne (Community Health and Social Services Network (CHSSN), 2014)
The Baseline Data Report Series is intended to serve as a resource that will allow local communities to better understand the demographic factors and health determinants affecting them and to assist institutional partners and community leaders in developing strategies to improve the well-being of their constituencies. The Baseline Data Report 2013-2014 (BDR) is the eleventh volume in the series.

Community Learning Centres : Changing Lives and Communities Annual Report of Activities - Leading English Education and Resource Network (LEARN) (2013)
This year the 37 Community Learning Centres across Quebec worked collaboratively with more than 700 local, regional, provincial, and national partners, to leverage in excess of $3 million of in-kind services and resources to serve their schools and communities. CLCs are doing more than just leveraging resources; they are changing lives and communities. They serve as a place for education and community development, and have become an important part of collaborative community change efforts. The stories and best practices highlighted in this annual report capture the essence of the initiatives being implemented by CLCs to achieve change and progress in English speaking communities across Quebec. Highlights of the activities undertaken in 2012-2013 begin with how one of our most important stakeholder groups, our teachers, are engaging with our initiative. The Community-Based Learning approach is just one example of the many strategies CLCs are adopting to impact students and develop a culture of lifelong learning. This year’s activities also included many examples of in-school and after-school activities in which CLC students are learning about incorporating healthy living options into their lives as well learning about aboriginal culture and building relationships between aboriginal and non-aboriginal communities. CLCs mobilize community and partner support to address current and important needs in our schools, including improving school climate and reducing bullying. Their activities for adults and seniors demonstrate to students that learning truly is a lifelong process. Engaging parents before their children have even entered school and continuing to find ways to connect and support parents throughout school life is an ongoing and important part of our work.

June 13, 2013 - Leading English Education and Resource Network (LEARN) (2013)

Update - Leading English Education and Resource Network (LEARN) (2012)

2009-10 Annual Report - Leading English Education and Resource Network (LEARN) (2010)
In a province as vast as Quebec, and with schools and school boards scattered over an enormous geographic expanse, the notion of bringing people together to create a COMMUNITY of collaboration may appear daunting, if not impossible. In reality, when people share similar interests and common goals, those physical impediments can quickly disappear. This is especially true when the ultimate objective is the academic success of our children in elementary and high schools. LEARN’s focus is to serve as a catalyst and facilitator for the creation of communities of collaboration composed of educators, parents and students across the province. It is our organization’s objective to make every effort possible to get the well-intentioned forces within the English educational milieu together to share the wealth of knowledge and experience that resides there.

Rapport Annuel 2009-2010 - Leading English Education and Resource Network (LEARN) (2010)
Dans une province aussi vaste que le Québec, où les écoles et les commissions scolaires sont dispersées sur une immense étendue géographique, la notion de rassembler les gens pour en faire une COMMUNAUTÉ de collaboration semble un obstacle gigantesque, sinon insurmontable. Dans la réalité, les gens partagent des intérêts similaires et des objectifs communs et cette notion d’impossibilité physique s’estompe rapidement. Cette évolution est particulièrement vraie quand l’objectif ultime est la réussite scolaire de nos enfants au niveau des écoles élémentaires et secondaires. LEARN a pour objectif de servir de catalyseur et de facilitateur pour la création de communautés de collaboration réunissant les éducateurs, les parents et les élèves à l’échelle de la province. L’objectif de notre organisation est de déployer tous les efforts possibles pour réunir les forces positives du milieu éducatif anglophone afi n de contribuer au partage des connaissances et des expériences disponibles au sein de notre communauté.